SUPERVISION OF THE USE OF FOREIGN WORKERS (TKA) IN THE FRAMEWORK OF REALIZING TECHNOLOGY TRANSFER AND SKILL TRANSFER FOR INDONESIAN WORKERS (TKI) - Lalu Husni; Ani Suryani Hamzah; RR. Cahyowati; Khairul Umam (PT. Radja Intercontinental Publishing, 2026)
The objective of this research is to identify and understand: (1) The regulation of monitoring the use of foreign workers (TKA) to facilitate the transfer of technology and expertise to Indonesian workers (TKI) acting as counterparts; (2) The monitoring of foreign workers' use based on current legislation to achieve the realization of technology and expertise transfer to Indonesian workers/counterparts; (3) The integrated monitoring norms that can facilitate the implementation of technology and expertise transfer to counterpart workers/TKIs. This research is normative legal research. The approaches used are (1) the statutory approach and (2) the conceptual approach. The types and sources of legal materials include primary legal materials, secondary legal materials, and tertiary legal materials. The research findings indicate that: (1) The monitoring of foreign workers' use for the purpose of technology and/or expertise transfer to accompany Indonesian workers has not been comprehensively regulated in accordance with the applicable legal hierarchy, and the norms for the implementation of education and/or training for accompanying Indonesian workers to facilitate technology and expertise transfer have not yet been included in the category of repressive judicial actions. (2) The current monitoring of the use of foreign workers has not yet achieved the realization of technology and expertise transfer to accompany Indonesian workers, as the existing regulations place the responsibility for technology and/or skills transfer entirely on the employing companies, without provisions for collaboration between employers and educational and training institutions. (3) The integrated monitoring norms that can realize the implementation of technology and/or expertise transfer to Indonesian workers acting as counterparts should involve not only Immigration and the Competency Certification Institute but also the Ministry of Education, Culture, Research, and Technology as the regulator to ensure that technology or expertise transfer has occurred according to the minimum competency standards for the positions occupied by foreign workers